(untitled) (Tempo e Argumento, 2025)
Through a qualitative analysis of case files from the French Juvenile Justice system, this article presents a case study on how specialists from observation canters (primarily psychiatrists, psychologists, and social workers) assessed juvenile delinquents exhibiting clear signs of psychological suffering resulting from bombings and racial repression during the Holocaust in World War II and the Nazi occupation of France, who passed through these institutions between 1945 and 1953. The analysis of the case files of Angèle and Olivier, direct victims of air raids, as well as those of Manès and Yann, two Jewish adolescents heavily affected by genocide, reveal a profound misunderstanding among specialists regarding the suffering of these youths. In some instances, the context of the war was entirely ignored or minimized in favor of interpretations that reinforced outdated stereotypes about juvenile delinquency, social prejudices, or gender archetypes. Often, the specialists even declared themselves incompetent to deal with these adolescents, leading to the invisibility of their war-related juvenile experiences, which were manifested in the anguish documented in the analysed sources. It concludes that, although the observation centers were envisioned as modern and scientific institutions aimed at assisting judges in breaking the repressive cycle of the French Juvenile Justice system, which entered a new era in 1945, they were ill-equipped to accommodate these war-affected and oppressed adolescents. Consequently, these institutions ended up reinforcing outdated psychiatric classifications and stereotypes of juvenile delinquency from the interwar period.